(untitled) (Swiss Medical Weekly, 2013)
Ultrasound (US) has become a useful tool in the detection of early disease, differential diagnosis, guidance of treatment decisions and treatment monitoring of rheumatoid arthritis (RA). In 2008, the Swiss Sonography in Arthritis and Rheumatism (SONAR) group was established to promote the use of US in inflammatory arthritis in clinical practice. A scoring system was developed and taught to a large number of Swiss rheumatologists who already contributed to the Swiss Clinical Quality Management (SCQM) database, a national patient register. This paper intends to give a Swiss consensus about best clinical practice recommendations for the use of US in RA on the basis of the current literature knowledge and experience with the Swiss SONAR score. Literature research was performed to collect data on current evidence. The results were discussed among specialists of the Swiss university centres and private practice, following a structured procedure. Musculoskelatal US was found to be very helpful in establishing the diagnosis and monitoring the evolution of RA, and to be a reliable tool if used by experienced examiners. It influences treatment decisions such as continuing, intensifying or stepping down therapy. The definite modalities of integrating US into the diagnosis and monitoring of RA treatments will be defined within a few years. There are, however, strong arguments to use US findings as of today in daily clinical care. Some practical recommendations about the use of US in RA, focusing on the diagnosis and the use of the SONAR score, are proposed.